Penggunaan Al Aiming Reduction Forceps dan Toogling Rode yang Dimodifikasi dalam Penanganan Displasia Coxo Femoral (Hip Displasia) pada Anjing Golden Retriever - Dhirgo Adji; R. Aria Aji Brameswara (Jurnal Sain Veteriner, 2023)
AbstractSurgical treatment of coxo-femoral dysplasia (CFD) is quite difficult. The use of al aiming reduction forceps in the installation of toogling rode is an alternative method that can be further developed for handling CFD without osteotomy of the femoral head (FHO). The combination among good action, appropriate treatment and rehabilitation therapy could be ideal step for better recovery of patients with CFD. Complete recovery in this case occurred at 4 months postoperatively, and the dog is currently in normal condition, able to stand and walk very well. Key words : CFD, al aiming reduction forceps, toogling rode, FHO, rehabilitation